2014
DOI: 10.1080/13546805.2014.940886
|View full text |Cite
|
Sign up to set email alerts
|

Confabulations in schizophrenia

Abstract: Introduction Current theories of confabulation are based primarily on observation of neurological patients. The present paper evaluates these theories based on evidence from schizophrenia. Schizophrenia is unique in that it presents with a pathophysiology which differs from that of other neuropsychiatric conditions, and yet the candidate deficits various theories of confabulation implicate are often simultaneously present in schizophrenia. Methods A selective review of literature on schizophrenic and neurolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Regarding social cognition, the data remain inconsistent ( Green et al, 2008 ). Some studies have found evidence of alterations in these probands compared with normal controls ( Janssen et al, 2003 ; Bediou et al, 2007 ; Lavoie et al, 2013 ; Cella et al, 2015 ), whereas other studies have shown no differences at all ( Kelemen et al, 2004 ; Loughland, 2004 ). Similar deficits have also been observed both in unaffected first-degree relatives high in schizotypy ( Chen et al, 1998 ; Laurent et al, 2000 ; Vollema and Postma, 2002 ) and in healthy individuals that have reported psychotic-like experiences (PLEs; Kelleher and Cannon, 2011 ).…”
Section: Introductionmentioning
confidence: 90%
“…Regarding social cognition, the data remain inconsistent ( Green et al, 2008 ). Some studies have found evidence of alterations in these probands compared with normal controls ( Janssen et al, 2003 ; Bediou et al, 2007 ; Lavoie et al, 2013 ; Cella et al, 2015 ), whereas other studies have shown no differences at all ( Kelemen et al, 2004 ; Loughland, 2004 ). Similar deficits have also been observed both in unaffected first-degree relatives high in schizotypy ( Chen et al, 1998 ; Laurent et al, 2000 ; Vollema and Postma, 2002 ) and in healthy individuals that have reported psychotic-like experiences (PLEs; Kelleher and Cannon, 2011 ).…”
Section: Introductionmentioning
confidence: 90%
“…Several age-related cognitive functioning domains are afflicted in schizophrenia spectrum disorders, including short-term and working memory, executive function, disturbances of self-reflection, selfperception and insight, as well as emergence of confabulations (i.e., memory disturbances, involving the production of fabricated, distorted or misinterpreted memories about oneself or the world, without conscious intention to deceive). Neurogenesis, neurotrophism, and neurotransmission are affected in brain (i.e., PFC, medial temporal cortex and cortico-limbic structures) and in non-central systems (i.e., immunoinflammatory systems, insulin sensitivity) (Gómez et al 2014;Harvey 2014;Shakeel and Docherty 2015;Young and Geyer 2014). Also affected are neural networks of several brain regions, including the frontal cortex and temporal cortex, hippocampus, and subcortical regions (Kupenberg and Heckers 2000).…”
Section: Exercise Alleviation Of Regional and Cognitive Deficitsmentioning
confidence: 98%
“…Evaluating the various theories requires examining confabulations in a condition that presents with confabulations as well as deficits in the cognitive/metacognitive functions implicated by the various theories, like schizophrenia. Schizophrenia patients present with deficits in executive functioning, memory, source monitoring, and verbal comprehension, all of which have been implicated in confabulations (for detailed review, see Shakeel & Docherty, 2015). Examining confabulations in schizophrenia is also important because it has a pathophysiology that differs from other neuropsychiatric conditions and any functional theory of Correspondence and reprint requests to: Department of Psychology, University of Calgary, Calgary, Alberta, T2N 1N4, Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Examining confabulations in schizophrenia is also important because it has a pathophysiology that differs from other neuropsychiatric conditions and any functional theory of Correspondence and reprint requests to: Department of Psychology, University of Calgary, Calgary, Alberta, T2N 1N4, Canada. E-mail: mshakeel@kent.edu confabulation should be able to account for its presence anywhere, not just in some neuropsychiatric conditions (Shakeel & Docherty, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation